If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 54 = 2x Solving 54 = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 54 + -2x = 2x + -2x Combine like terms: 2x + -2x = 0 54 + -2x = 0 Add '-54' to each side of the equation. 54 + -54 + -2x = 0 + -54 Combine like terms: 54 + -54 = 0 0 + -2x = 0 + -54 -2x = 0 + -54 Combine like terms: 0 + -54 = -54 -2x = -54 Divide each side by '-2'. x = 27 Simplifying x = 27
| 5x+37=13x-51 | | 2x+59=8x+11 | | 16-6n=22 | | -9-3-20x=-52 | | 7n+12n=n-6 | | 5x+35=12x-21 | | 9x-10=6x+2 | | 5(v+2)+3(v-5)=19 | | (2m+9)=15m-9 | | 8n-(5n+13)=7 | | 3m+2=5(m-1) | | 3y+12=28 | | 3-(3m-7)=43 | | 15d-12=68 | | 6y^3-y^2-2y=0 | | 14x^2+11x+3=2x^2-3x+3 | | -3y+17=3y-10 | | 6x+3=24x+18 | | 3p+2e=5.75 | | 48n^3=147n | | .36m^2=121 | | 12x-1=3+5x | | 5+2x=10x+4 | | 10p-2=4p+7 | | 4+5f=7+3f | | 4x+48= | | 6u=-15 | | 3b^3-27b=0 | | 4+5x=7+3f | | LO=RT | | 7t-12=3t-5 | | 3+6x=7+3x |